2012
DOI: 10.1021/bc3002997
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photodynamic Efficacy of Zinc Phthalocyanine by Conjugating to Heptalysine

Abstract: Zinc phthalocyanine (ZnPc) is a promising photosensitizer for photodynamic therapy, but faces some challenges: ZnPc is insoluble in water and thus requires either special formulation of ZnPc by, e.g., liposome or Cremophor EL, or chemical modification of Pc ring to enhance its bioavailability and photodynamic efficacy. Here, we conjugated monosubstituted ZnPc-COOH with a series of oligolysine moieties with different numbers of lysine residues (ZnPc-(Lys)(n) (n = 1, 3, 5, 7, 9) to improve the water solubility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…This is likely due to the relatively low light doses (1.5 or 3 J / cm 2 ) used in the study. We have previously shown that cells can recover from limited redox damage 53.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to the relatively low light doses (1.5 or 3 J / cm 2 ) used in the study. We have previously shown that cells can recover from limited redox damage 53.…”
Section: Resultsmentioning
confidence: 99%
“…This is not too surprising. It is often observed that PSs like CPZ can be taken up by cells probably due to the hydrophobic nature of most PSs 53, 54. In the case of HSA:CPZ, it is likely that HSA undergoes a conformational change on tumor cell surfaces and sheds out the CPZ, which is then taken up by tumor cells through non-specific pinocytosis process.…”
Section: Resultsmentioning
confidence: 99%
“…In the special case of zinc phthalocyanine (ZnPc), successful conjugation with different nanocarriers has already been demonstrated in many other studies [25,[29][30][31][32][33][34][35][36], and dendritic delivery of PDT agents has been investigated within the last few years to improve upon tumour selectivity, retention and pharmacokinetics [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a useful method for the treatment of various cancers [1][2][3][4]. PDT involves the use of photochemical reactions mediated through the interaction of photosensitizers (PSs) and appropriate light to generate ROSs and cause irreversible photodamage to tumor cells [5][6][7].…”
mentioning
confidence: 99%
“…Then ZS-ZnPc compound shows extreme photostability upon the irradiation. 1 O 2 is a vitally important species of ROSs for PSs in photodynamic cancer therapy, photooxidation of toxic molecules, and photoproduction of important intermediation for various chemicals because of its high oxidation ability [28]. ADMA was employed as a quencher to reflect the singlet oxygen generation ability of Pcs in aqueous [29,30].…”
mentioning
confidence: 99%